Breakdown and Partial discharge characteristics of Mineral oil-based nanofluids - Muangpratoom, Pichai; Pattanadech, Norasage (My University, 2018)
In this study, the AC breakdown (BD) voltages and partial discharge (PD) activities of mineral-oil (MO)-based nanofluids were investigated under controlled conditions. The aim of this research is to improve the dielectric properties of MO by amalgamation with various types of nanoparticles, i.e. semiconducting and dielectric nanoparticles. Two types of nanoparticles, i.e. titanium dioxide and barium titanate with mean diameters of < 100 nm were used in the nanofluid samples prepared for the experiments. The AC BD voltages of the nanofluids were investigated according to IEC 60156. In addition, PD characteristics of the MO-based nanofluids were examined including PD inception voltage (PDIV) characteristics and PD activity with a needle-plane electrode configuration. The test circuit was set up in accordance with IEC 60270 and the experiment was performed in conformity with IEC 61294 at room temperature. The test results showed that the AC BD voltages of the modified liquids were clearly influenced by the type of nanoparticles added, with the AC BD voltages of the MO with nanoparticles being slightly higher than those of the unmodified MO used for comparison. Furthermore, the nanoparticles also demonstrated a propensity to increase the PDIV of the nanofluids compared with the PDIV of the MO.